Kelayakan Upah Buruh Tani Perkebunan Kelapa Sawit Pt. Sawit Mandiri Lestari Kalimantan Tengah - Agustina Irene Mantolas; Widi Artini; Wiwiek Andajani (Universitas Kadiri, 2022)
Oil palm (Elaeis guneensis Jacq.) is a plant that is grown and processed, one of which is used as cooking oil. In 2016, 52.1 million tons were utilized for consumption. It is estimated that this will continue to increase to 68 million tons in the future. Indonesia is part of the largest producer in the world, producing 50% of the world's total production in 2021. The average amount of production can meet the standard of wages for laborers for manual workers on plantations. palm. This research was conducted by the author in Bukit Indah Village, Lamandau District, Bulik Regency, Central Kalimantan. The data was used in the form of primary data and secondary data. Primary data was obtained from farmers through a list of questions that had been prepared, while secondary data was obtained from PT. The Independent Sustainable Palm Oil. The sampling method used purposive sampling by taking a sample of 30 farmers. The results of this study indicated the income of oil palm farmers at PT. Independent sustainable palm oil was profitable and feasible because the amount of income was higher than the amount of agricultural expenditure. This shows that in terms of human resources, the palm oil production company at PT. Sawit Mandiri Lestari was sustainable, it had the potential to take advantage of oil palm cultivation.